Perception versus reality: A National Cohort Analysis of the surgery‐first approach for resectable pancreatic cancer. (21st July 2021) - Bergquist, John R.; Thiels, Cornelius A.; Shubert, Christopher R.; Ivanics, Tommy; Habermann, Elizabeth B.; Vege, Santhi S.; Grotz, Travis E.; Cleary, Sean P.; Smoot, Rory L.; Kendrick, Michael L.; Nagorney, David M.; Truty, Mark J.
Abstract: Introduction: Although surgical resection is necessary, it is not sufficient for long‐term survival in pancreatic ductal adenocarcinoma (PDAC). We sought to evaluate survival after up‐front surgery (UFS) in anatomically resectable PDAC in the context of three critical factors: (A) margin status; (B) CA19‐9; and (C) receipt of adjuvant chemotherapy. Methods: The National Cancer Data Base (2010–2015) was reviewed for clinically resectable (stage 0/I/II) PDAC patients. Surgical margins, pre‐operative CA19‐9, and receipt of adjuvant chemotherapy were evaluated. Patient overall survival was stratified based on these factors and their respective combinations. Outcomes after UFS were compared to equivalently staged patients after neoadjuvant chemotherapy on an intention‐to‐treat (ITT) basis. Results: Twelve thousand and eighty‐nine patients were included ( n = 9197 UFS, n = 2892 ITT neoadjuvant). In the UFS cohort, only 20.4% had all three factors (median OS = 31.2 months). Nearly 1/3rd (32.7%) of UFS patients had none or only one factor with concomitant worst survival (median OS = 14.7 months). Survival after UFS decreased with each failing factor (two factors: 23 months, one factor: 15.5 months, no factors: 7.9 months) and this persisted after adjustment. Overall survival was superior in the ITT‐neoadjuvant cohort (27.9 vs. 22 months) to UFS. Conclusion: Despite the perceived benefit of UFS, only 1‐in‐5 UFS patients actually realize maximal survival when known factors highly associated with outcomes are assessed. Patients are proportionally more likely to do worst, rather than best after UFS treatment. Similarly staged patients undergoing ITT‐neoadjuvant therapy achieve survival superior to the majority of UFS patients. Patients and providers should be aware of the false perception of 'optimal' survival benefit with UFS in anatomically resectable PDAC. Abstract : Survival of resectable pancreatic cancer patients treated with surgery and stratified by margin status, CA19‐9 levels, and chemotherapy receipt shows survival is highly predicted by these factors and is proportionally not ideal in the majority of undergoing an upfront resection strategy. Neoadjuvant chemotherapy offers significant benefit to upfront surgery in the context of acheiving optimal survival in the context of these factors.